Uma análise de deslocamento cultural na obra de William Foote Whyte sociedade de Esquina - Fabiane, Storck Damaris; Janzen, Henrique Evaldo [UNESP] (My University, 2014)
The article shows an intercultural analysis of the book Street Corner Society written by the author and researcher William Foote Whyte. The aim is identify some evidence of the author's cultural dislocation during his ethnographic research and understand the relations between two different cultures. The categories of analysis used in this paper - duplication of the other, hybrid constructions and exotopy - express the movements of the approximation between the researcher and the culture of the field, and are based in the dialogs between Bakhtin and the interculturalism. The article contrasts the importance of the cultural dialogue for a comprehension of the other culture, specially, in the contexts of the ethnographic researches.
An analysis of cultural dislocation in the William Foote Whyte's work street Corner Society
Keywords: Cultural dislocation; Ethnographic research; Interculturalism